Couturières de Santos. Personnification mythique et manipulation rituelle des images sacrées à Mexico D.F. : le cas du Niño Dios et de la Santa Muerte - Silvia Mancini (Nuevo mundo - Mundos Nuevos, 2015)
In certain streets of the Centro Historico of Mexico, the density of shops and cloth markets and adornments, of haberdashery products and various accessories designed to embellish the parade suits and festive costumes is not for human beings only. These very streets overflowing with goods are patronized also by the seamstresses (dressmakers) of Santos, that is, of the sacred images they are the object of a fervent devotion in the Distrito Federal. Based upon the history of some exemplary life courses of a few such seamstresses, this contribution tries to put in perspective a feminine know-how not limited to the technical skills that are those of inventive tailors and dressmakers. They are, themselves, devotees to the image which they clothe in precious garments, and with which they cultivate a singular relationship. Two types of challenges or issues, both economical and symbolic, arise from that practice which consists in clothing los Santos – and more particularly the Niño Dios et the Santa Muerte. First, on the economical level, the activity linked to the making of ritual clothes involves the raising of some small capital, and a parallel economy of a stupendous scope. Second, on the symbolic level, observing how the clothing of these two sacred images was made has highlighted the ‘psychotechnical’ implications operating in the ritualized treatment of clothed images.